Physics Concepts Based Data Centre Operations: A Medium for Education on Energy Efficiency and Technological Innovations - Hughes, Stephen William; Schouten, Peter (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
Data centres are considered the exclusive sites of information technology and computer science. However, many aspects of their day-to-day operation can be used to teach important concepts in physics, such as heat transfer, AC and DC power transmission, fibre optic transmission, energy loss in transmission cables, and electronic componentry. Data processing requirements and power usage in data centres are growing exponentially, and therefore, solutions need to be developed to reduce energy costs, given the challenges of global warming. To this end, work is being done on storing data in strands of DNA. An experiment to measure the change in temperature of air passing through an internet hub is described as a means of teaching students about the physics of data centres. The procedure and calculations shown in this particular experiment can be used and applied by secondary school physics students to evaluate the energy budget and efficiency of different data centres, such as those used at their school. In addition, this article details how students can make simple calculations that directly show how novel DNA data storage technology can be utilized to reduce the amount of hardware and power used at data centres. The potential for quantum computing to reduce the power requirements of data centres is also discussed.